2015
DOI: 10.1161/hypertensionaha.115.06303
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale Closure in Obstructive Sleep Apnea Improves Blood Pressure and Cardiovascular Function

Abstract: O bstructive sleep apnea (OSA) is characterized by intermittent hypoxemia and associated with increased prevalence of vascular dysfunction and arterial hypertension, but the underlying mechanisms are incompletely understood.1 In OSA, apneas are related to excessive throat muscle relaxation with consequent inspiratory efforts against the closed glottis, finally resulting in the patient's arousal associated with sympathetic activation and hyperventilation. The hyperventilation, in turn, contributes to the next a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Patent foramen ovale has been demonstrated to have a higher prevalence in patients with obstructive sleep aponoea compared to healthy controls, and is suspected to inrease nocturnal oxygen desaturation in these patients [ 42 ] and to enhance other pathologic conditions associated with OSA [ 43 ]. In both scuba and apnoea divers knowledge about the implications of a patent foramen ovale regarding incidence and severity of decompression sickness is scarce [ 44 ], especially because it is unkown if recurrent decompression sickness is a result of a patent foramen ovale, the inabiliy to adopt a more conservative diving style, or both [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patent foramen ovale has been demonstrated to have a higher prevalence in patients with obstructive sleep aponoea compared to healthy controls, and is suspected to inrease nocturnal oxygen desaturation in these patients [ 42 ] and to enhance other pathologic conditions associated with OSA [ 43 ]. In both scuba and apnoea divers knowledge about the implications of a patent foramen ovale regarding incidence and severity of decompression sickness is scarce [ 44 ], especially because it is unkown if recurrent decompression sickness is a result of a patent foramen ovale, the inabiliy to adopt a more conservative diving style, or both [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Searching for the presence of a PFO by transoesophageal echocardiography, which is possible under field conditions, could have been not only of mechanistic but also of therapeutic importance in this high-altitude population living under remote conditions, among which classical treatment of sleep-disordered breathing with continuous positive airway pressure (CPAP) therapy might not be possible for technical reasons. Indeed, in analogy to recent observations in patients with sleep apnoea syndrome at low altitude [3], it appears possible that PFO closure may attenuate pulmonary (and systemic) hypertension and improve sleep-disordered breathing in Kyrgyz high-altitude dwellers.…”
mentioning
confidence: 75%
“…A recent retrospective longitudinal multicenter study of 199 patients, “DysrhythmiAs in patieNts with congenitAl heaRt diseAse” (DaNaRA), demonstrated that patients with congenital heart disease, particularly patients with complex defects, develop AF at a young age and progress frequently from paroxysmal AF to (long-standing) persistent/permanent AF ( 91 ). Sixteen patients (8%) experienced a cerebrovascular event 14 ( 2 33 ) years before the first documented AF. The total incidence of TIA/stroke in the population was 13%.…”
Section: Discussionmentioning
confidence: 99%
“…The Paradoxical Emboli from Large Veins in Ischemic Stroke (PELVIS) study confirmed that patients with cryptogenic stroke have an increased prevalence (20%) of pelvic deep venous thrombosis ( 8 ). Cryptogenic stroke also seems to be associated with vigorous or strenuous exercise, decompression illness, sneezing, coughing, obstructive sleep apnea, and even migraine ( 9 17 ).…”
Section: Introductionmentioning
confidence: 99%